Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.11591/ijere.v9i4.20505
|View full text |Cite
|
Sign up to set email alerts
|

Development of an assessment tool for mathematical reading, analytical thinking and mathematical writing

Abstract: <p>The main objective of this research was to develop and validate the quality of an assessment tool for evaluating the mathematical reading, analytical thinking, and mathematical writing skills of fourth-grade students. We randomly selected 222 fourth grade students across multiple schools of varying sizes to take the assessment. Multidimensional Random Coefficients Multinomial Item Response Model was applied to validate the quality of the developed assessment tool. A design-based research methodology w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…The Institute for the Promotion of Teaching Science and Technology (2014) reported that Thai students are considered poor when it comes to learning mathematics and science because both subjects act as a basis for our regular practice (Gravemeijer, 1998cited in Leher, 2007. Moreover, Kesorn et al (2020) revealed that while they are teaching Thai mathematics teachers do not usually connect students' regular existence practices with resolving mathematical problems. This is supported by Jaikla et al (2021) who stated that the conventional teaching approach was botched when it came to associating student knowledge with their lived experience.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The Institute for the Promotion of Teaching Science and Technology (2014) reported that Thai students are considered poor when it comes to learning mathematics and science because both subjects act as a basis for our regular practice (Gravemeijer, 1998cited in Leher, 2007. Moreover, Kesorn et al (2020) revealed that while they are teaching Thai mathematics teachers do not usually connect students' regular existence practices with resolving mathematical problems. This is supported by Jaikla et al (2021) who stated that the conventional teaching approach was botched when it came to associating student knowledge with their lived experience.…”
Section: Problem Statementmentioning
confidence: 99%
“…According to Chaona et al (2021), after they have practiced the TLSOA model, pre-service mathematics teachers can generate problem conditions that are associated with the students' real realm, examine the setting of the problem situation, identify keywords that relate to students' thoughts, can foresee students' thoughts and can formulate instruction resources to back up such thoughts. Following this line of reasoning, the TLSOA model entails incorporating students' regular existence practices in coming up with problem conditions for students to deal with actual knowledge as mentioned by many scholars (Chaona et al, 2021;Dudley et al, 2019;Jaikla et al, 2021;Kesorn et al, 2020) should be utilized in current educational demand.…”
Section: Problem Statementmentioning
confidence: 99%
“…Its focus is on analytical thinking skills and competency in active citizenship with global mindedness. To do so, the researcher considers the consistency and coverage of the curriculum and appropriate assessment tools [15], by connecting the curriculum to create interactions between teachers and students, and parents and community.…”
Section: Introductionmentioning
confidence: 99%
“…All educational activities are inseparable from the use of digital technology [22][23]. In the teaching and learning process in schools, the very important thing to do is assessment [24][25]. At this time there are still many teachers who use the conventional assessment system.…”
Section: Introductionmentioning
confidence: 99%